Non-invasive motor cortex stimulation effects on quantitative sensory testing (QST) in healthy and chronic pain subjects: a systematic review and meta-analysis - Giannoni-Luza, Stefano (Pain, 2020)
One of the potential mechanisms of motor cortex stimulation by non-invasive brain stimulation (NIBS) effects on pain is through the restoration of the defective endogenous inhibitory pain pathways. However, there is still limited data on quantitative sensory testing (QST), including conditioned pain modulation (CPM), supporting this mechanism. This systematic review and meta-analysis aimed to evaluate the effects of non-invasive motor cortex stimulation on pain perception as indexed by changes in QST outcomes. Database searches were conducted until July 2019 to included randomized controlled trials that performed sham-controlled NIBS on the motor cortex in either healthy and/or pain population and assessed the QST and CPM. Quality of studies was assessed through the Cochrane tool. We calculated the Hedge’s effect sizes of QST and CPM outcomes, their 95% confidence intervals (95% CI) and performed random-effects meta-analyses. Thirty-eight studies were included (1178 participants). We found significant increases of pain threshold in healthy subjects (ES=0.16, 95% CI=0.02 to 0.31, I(2)=22.2%) and pain population (ES=0.48, 95% CI=0.15 to 0.80, I(2)=68.8%); and homogeneous higher CPM effect (pain ratings reduction) in healthy subjects (ES=−0.39, 95% CI=−0.64 to −0.14, I2=17%) and pain population (ES=−0.35, 95% CI=−0.60 to −0.11, I2=0%) in active NIBs group compared with sham. These results support the idea of top-down modulation of endogenous pain pathways by motor cortex stimulation as one of the main mechanisms of pain reduction assessed by QST, which could be a useful predictive and prognostic biomarker for chronic pain personalized treatment with NIBS.